PENGARUH SIZE, LEVERAGE, PROFITABILITY, INVENTORY INTENSITY, CORPORATE GOVERNANCE, DAN CAPITAL INTENSITY RATIO TERHADAP MANAJEMEN PAJAK (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Rizky Wijayanti; Dul Muid (Diponegoro Journal of Accounting, 2020)
This study aims to examine the factors that affect the company’s management taxations using effective tax rate as an indicator. There are several factors used in this research consisted of size, leverage, profitability, inventory intensity, corporate governance, and capital intensity ratio. The purpose of this study is to empirically examine whether size, leverage, profitability, inventory intensity, corporate governance, and capital intensity ratio affect the taxations management in manufacturing companies listed in Indonesia Stock Exchange. The analysis technique that being used to test the hypotheses is multiple linear regression analysis. The result shows that inventory intensity disclosure has significant on taxations management, size, leverage, profitability, corporate governance, and capital intensity ratio has no significant influence on taxations management.